Sound pressure level attenuation provided by thin rigid screens coupled to tall buildings - Tadeu, A. (2007)
This paper computes the sound pressure attenuation provided by thin rigid screens placed on the walls of a tall building to protect the building from the direct sound incidence produced by sound pressure sources placed in its vicinity. The problem is formulated in the frequency domain via the Traction Boundary Element Method (TBEM), which overcomes the thin-body difficulty arising with the classical Boundary Element Method (BEM) formulation. The building, the screens and the ground are assumed to be infinitely long and rigid. The Green's functions used in the TBEM formulation allow the solution to be obtained without discretizing the flat solid ground and vertical solid façade. Thus, only the boundary of each rigid screen is modelled, which allows the TBEM to be efficient even at high excitation frequencies. The hypersingular integrals that result from the implementation of the TBEM are computed analytically. The algorithm is verified using a BEM model, which incorporates the Green's functions for a full space, thus requiring the full discretization of the domain. The model developed is then used to simulate wave propagation in the vicinity of thin rigid screens with different dimensions and geometries. The two-dimensional (2D) and three-dimensional (3D) time and frequency responses and sound pressure attenuation results are both computed over grids of receivers placed perpendicular and parallel to the building wall.